The impact of Pandita training on the skill of performing Buddhist rituals - Budiyanto; Taridi (SMARATUNGGA: JURNAL OF EDUCATION AND BUDDHIST STUDIES, 2021)
This study aims to explore the impact of pandita training on the skill of performing Buddhist rituals. Rituals or ceremonial acts are not inherently religious. Rituals play a role in relieving social pressures and strengthening the collective bonds of a group. Rituals are performed in various forms, including the tradition of lighting candles or incense, wearing certain clothes, and sitting, standing, or kneeling during praying. The most common of all rituals is the initiation ceremony which marks a stage in the human life cycle. The type of research used in this study is descriptive quantitative research. The data analysis technique was carried out in several stages, including the following: 1) validity test technique to determine the validity of the moment item, using product moment analysis; 2) the instrument's reliability test uses the Alpha formula; 3) simple regression model is chosen to measure the effect of religious training variable (X) on skills to lead religious activities (Y). Based on data analysis, it can be concluded that the training of Pandita can improve the skills of Pandita in performing rituals.